Hubungan Lamanya Menjalani Hemodialisis dengan Kualitas Tidur Pasien Gagal Ginjal Terminal di Rumah Sakit Advent Bandung - Imanuel Sri Mei Wulandari; Sari Fatimah (Jurnal Medika Cendikia, 2016)
End stage renal failure (ESRD) has got higher prevalence this days, it needs special attention by all health providers. There are 44-83% of end stage renal failure that experience sleep alteration, this alters their daily wellness and affect their quality of life. This study aimed to seek the relationship between length of hemodialysis and sleeping quality on end stage renal failure patients by means PSQI questioner (Pittsburgh sleep quality index). Research design is correlation analysis with cross sectional design to 64 end stage hemodialysis patient in Bandung Adventist hospital. Male patients are more in number to female, where the prevalence ratio is 1,4:1. Age span is 25-80 years old, and age average is 53,3 years, where the higher age frequency is 56-65 years. Length span hemodialysis is 1-99 months, average length is 36 months. There are 20 patients that have good quality of sleeping (31,3%).in the other hand, there are 44 patients have bad quality of sleeping (68,7%). Conclusion: there are no correlation between length of hemodialysis and sleeping quality on end stage renal failure.